'An Old Maid in a House Is the Devil': Single Women and Landed Estate Management in Eighteenth‐Century England. (29th December 2021) - Shields, Sarah
Abstract: This article examines the impact of singleness on elite women's experiences of landed estate management in eighteenth‐century England. Through extensive archival research, the article argues that singleness directly impacted women's relationships with landed estates and their ability to manage and shape their physical landscape. The article reveals that single women were overseeing the management of vast family estates: work that too often went unrewarded in their own lifetime and unrecognised in subsequent estate histories, due in large part to their unmarried status. It offers a fresh understanding of landed estates and will be of interest to historians and historical geographers alike.